Coupling Photochromism and Charge Transport in π-Extended Arylazo Oligothiophenes and Oligothienoacenes - Chiara Taticchi; Federico Nicoli; Mattia Zangoli; Filippo Monti; Eugenio Lunedei; Alessandro Turci; Massimiliano Curcio; Pierluigi Mondelli; Mario Caironi; Magda Monari; Massimo Gazzano; Andrea Candini; et al. (Journal of the American Chemical Society, 2026)
Abstract Developing photoresponsive molecular materials that couple efficient charge transport with robust photoswitching remains challenging because structural features enhancing one function often compromise the other. In this study, two homologous series of arylazo oligothiophenes and oligothienoacenes–in which an azo photoswitch is directly conjugated to a π-extended thiophenic scaffold–were systematically investigated. Ultraviolet–visible (UV–vis) spectroscopy combined with theoretical calculations shows that, in solution, π-extension enables E → Z photoisomerization using visible light but concurrently lowers the barrier for thermal Z → E back-conversion by activating rotational isomerization pathways. Aryl fluorination counteracts this effect by strengthening intramolecular S(n)···π interactions, extending the Z-isomer half-life from minutes to hours. In the solid state, π-extension promotes dense intermolecular packing that inhibits photoisomerization. Introduction of a bulky trityl group reduces packing density, as revealed by single-crystal analysis, restoring E ⇆ Z photochromism in crystalline thin films and inducing a crystalline-to-amorphous transformation, as evidenced by X-ray diffraction (XRD) and microscopic analysis. The resulting light-driven molecular and morphological reorganization enables reversible, light-induced modulation of electrical conductivity in two-contact planar devices. Space-charge-limited-current measurements show that conductivity changes correlate with isomer-dependent electron mobility properties. Overall, these findings establish π-extended azo-thiophene scaffolds as a versatile platform to couple photochromism and morphological reorganization with charge transport phenomena.